MEWUJUDKAN KEMANDIRIAN EKONOMI DESA MELALUI BARBERSHOP KARANG TARUNA BERBASIS KOMUNITAS - Tutik Heriana; Dendy Eta Mirlana; Lilik Prihatin; Anton Subagyo; Mohammad Abdul Munir; Ferdiansyah Surya Perdana; Fajar Bayu Widodo (Jurnal Abdi Insani, 2026)
Balanced economic development between rural and urban areas is crucial for improving community welfare, especially in rural areas. Many rural areas still depend on the agricultural sector or traditional village businesses. Pijeran Village has human resource potential in the form of youth organisations with skills in hairdressing. Based on observations and interviews, the problems faced are 1) Lack of support in barbershop management. 2) No efforts to develop the barbershop business. The objectives of the activity are 1) To improve barbershop management knowledge. 2) To develop the barbershop business. The community service method used is the Participatory Action Research method using Participatory Rural Appraisal, which focuses on empowerment. The stages in PAR are knowing, understanding, planning, taking action to solve problems, and change. The action programme implementation consists of adding technological tools and innovations, socialising barbershop management and business feasibility study workshops, realising simulation demonstrations and practical application of technological tools and innovations by barbershop instructors, and realising effective marketing strategies. The results of the implementation are the addition of assets for partners in the form of technological tools and innovations, increased knowledge of barbershop management, increased knowledge of business feasibility study analysis, and increased skills as a result of demonstrations and practical application of technological tools and innovations, and the realisation of effective marketing strategies. The impact of technology implementation is to improve the quality and professionalism of barbershop services, expand market reach, increase income and economic independence, and foster an entrepreneurial culture.